ANALISIS PERAN MEDIA SOSIAL DALAM PELAKSANAAN PEMBANGUNAN NASIONAL - novliza eka patrisia (Prodi Ilmu Komunikasi Universitas Putera Batam, 2021)
This paper is the result of analysis and observation that reviews the use of social media in the form of social networks as a very effective medium for communication and information to convey problems or aspirations of the community, especially for areas that have not been maximally touched by media and are not widely known by the wider community in particular. current regional officials. This paper aims to describe the characteristics of digital societies that use social media. Then, describe the relationship between social media and national development and describe the opportunities and challenges that arise in the digital era. This research method is a descriptive study using qualitative analysis. The results of the research show that national development will be realized well if a social media in the form of social networks is used by the community properly, ethically and can be justified. Therefore the role of local government is very important in informing the community quickly and accurately.